Puntos nociceptivos de la articulación temporomandibular y postura, en usuarios con trastornos temporomandibulares asistentes a un centro odontológico de Cartagena (2018)
INTRODUCTION: The temporomandibular joint is a complex unit that works together with the different muscular, ligamentous, and joint structures that surround it in a harmonious way, to maintain the stability of the cranio-cervico-mandibular complex; This stability could prevent future alterations both bodily and temporomandibular that affect the functionality of the individual. It is important to perform an early detection of signs and / or symptoms that can alter this system through a postural and ATM assessment. GENERAL PURPOSE. To determine the nociceptive points of the TMJ and posture in users with diagnosis of temporomandibular disorders, in a dental center of Cartagena. METHODS: A cross-sectional descriptive study was carried out; which investigated the presence of the exhibition and the acuteness of the event that makes up the population to be studied where only one measurement was made over time in each subject. (46) The study population consisted of users attending the Orthodontic Clinic, in the Dentistry faculty of the University of Cartagena, women and men with an age range between 5 and 65 years. The choice of sample for this study was at convenience, this leads to samples within the individual elements and groups of randomly selected elements within the population. RESULTS: Within the investigation, a higher prevalence was evidenced in the population that presented a joint diagnosis, which showed greater rotation of the iliac crests anteriorly. The most frequent nociceptive points in the population in the evaluations of both male and female gender were points 1, 2, and 3 in the patients, who at the end of the evaluation. He was exposed to several commendations with functional exercises that avoid prolonging bad habits and maintaining good postural hygiene.